Examining Opportunities for Implementing Blended Learning in Physical Education Learning at SMA Negeri 9 Semarang - Rahayu Ngudi Sari; Muh. Isna Nurdin Wibisana; Priyo Hutomo; Bertika Kusuma Prastiwi (Universitas Sebelas Maret, 2024)
This study investigates the potential implementation of blended learning in Physical Education, Sports, and Health (PJOK) at SMA Negeri 9 Semarang. Blended learning, which combines traditional face-to-face instruction with online learning components, offers a balanced educational experience that addresses the challenges posed by traditional PJOK teaching methods. The research involved qualitative data collection through interviews, observations, and documentation, supported by literature reviews on blended learning in physical education. The findings reveal that while students and teachers are proficient with gadgets and digital systems, the application of technology in PJOK is still limited. The main issues identified include students' difficulties with theoretical assessments and the predominance of practical over theoretical teaching. The study highlights the readiness of teachers to adopt digital tools and the availability of adequate infrastructure to support blended learning. The analysis connects these findings with previous research, demonstrating that blended learning can enhance learning outcomes and motivation in physical education. The study concludes that implementing self-directed blended learning, where theoretical content is delivered online and practical sessions are conducted offline, could effectively address the identified challenges and improve the overall PJOK learning experience at SMA Negeri 9 Semarang.